Prostatic morphological changes throughout life: Cytochemistry as a tool to reveal tissue aging markers - Guerra, Luiz Henrique Alves [UNESP]; Campos, Silvana Gisele Pegorin [UNESP]; Taboga, Sebastião Roberto [UNESP]; Vilamaior, Patricia Simone Leite [UNESP] (Wiley, 2024)
The prostate undergoes normal or pathological morphological changes throughout life. An understanding of these changes is fundamental for the comprehension of aging-related pathological processes such as benign prostatic hyperplasia (BPH) and cancer. In the present study, we show some of these morphological changes, as well as histochemical techniques like Weigert's resorcin-fuchsin method, Picrosirius Red, and Gömöri's reticulin for use as tools in the study of prostate tissue under light microscopy. For this purpose, prostates of the Mongolian gerbil (n = 9), an experimental model that develops BPH spontaneously, were analyzed at three life stages: young (1 month old), adult (3 months old), and old (15 months old). The results showed that fibrillar components such as collagen, and reticular and elastic fibers, change throughout life. In young animals, the prostate has cuboidal epithelium surrounded by thin layers of smooth muscle, continuous collagen fibers, winding reticular fibers, and sporadic elastic fibers. With adulthood, the epithelium becomes columnar, encircled by compacted muscle cells among slender collagen fibers, elongated reticular fibers, and linear elastic fibers. In aging individuals, the prostate's epithelium stratifies, surrounded by thick muscle layers among dense collagen fibers, disordered reticular fibers, and elastic fibers in different planes. We also identified a few accumulations of lipid droplets and lipofuscin granules in adult animals and high accumulation in old animals evidenced by Oil red O and Gömöri-Halmi techniques, respectively. The histochemical techniques presented here have been demonstrated to be useful and accessible tools in prostate studies. RESEARCH HIGHLIGHTS: Cytochemical techniques to study prostate morphology. The prostate changes with age.